2021
DOI: 10.1186/s40814-021-00792-5
|View full text |Cite
|
Sign up to set email alerts
|

Pain-guided activity modification during treatment for patellar tendinopathy: a feasibility and pilot randomized clinical trial

Abstract: Background Activity modification is a key component of patellar tendinopathy treatment but there is a lack of evidence guiding activity modification prescription. Use of activity modification in treatment studies has varied widely and the impact of those recommendations has not been directly investigated or compared. The purpose of this study was to assess (1) the feasibility of using pain-guided activity modification during treatment for patellar tendinopathy and (2) if our outcome measures ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
1
10
0
3
Order By: Relevance
“…Performance Test. As for vertical jump height, despite the fact that Sprague et al 35 reported a jump height improvement after 12 weeks, our data showed no change in vertical jump height, similar to other previous studies. 1,32 It is interesting to note that jump performance in our study population did not improve given that muscle strength and flexibility were both increased after exercise therapy; that may be because other factors, such as arm swing or trunk angle, can also affect vertical jump height.…”
Section: Association Between Physical Response and Clinical Improvementsupporting
confidence: 89%
“…Performance Test. As for vertical jump height, despite the fact that Sprague et al 35 reported a jump height improvement after 12 weeks, our data showed no change in vertical jump height, similar to other previous studies. 1,32 It is interesting to note that jump performance in our study population did not improve given that muscle strength and flexibility were both increased after exercise therapy; that may be because other factors, such as arm swing or trunk angle, can also affect vertical jump height.…”
Section: Association Between Physical Response and Clinical Improvementsupporting
confidence: 89%
“…Da es sich bei der Tendinopathie unabhängig von der betroffenen Körperregion um ein im Wesentlichen überlastungsinduziertes Beschwerdebild handelt, sollte das Management der Belastung adressiert werden. Hierfür hat sich das Pain Monitoring Model 15 bewährt. Solange die Patient*innen dessen Kriterien erfüllen, ist ihnen die weitere Ausübung ihrer Sportart erlaubt.…”
Section: Therapieunclassified
“…Am nächsten Morgen nach der Aktivität sollte auf der NRS ein Wert von 5 nicht überschritten werden und die Beschwerden sollten sich nicht von Woche zu Woche weiter verschlechtern 15 , 16 .…”
Section: Therapieunclassified
“…3 Tendon structure is associated with function and outcomes after injury, and may be readily assessed in a clinical setting. [4][5][6][7][8] Evaluating the structural changes in the injured patellar tendon may assist in identifying the underlying pathophysiology as well as guide clinical care after injury.Patellar tendinopathy (PT) is an overuse injury of the patellar tendon typically associated with activities involving plyometrics. 9,10…”
mentioning
confidence: 99%
“…One of the themes observed across pathological tendons, regardless of the source of injury, are morphological alterations (eg, tendon thickening, larger cross‐sectional areas, or hypoechoic regions identified on sonographic evaluations) to the tendon 3 . Tendon structure is associated with function and outcomes after injury, and may be readily assessed in a clinical setting 4–8 . Evaluating the structural changes in the injured patellar tendon may assist in identifying the underlying pathophysiology as well as guide clinical care after injury.…”
mentioning
confidence: 99%